Ecological Infrastructures on Road Networks in and around Forested Areas - Gülci, Sercan; Akay, Abdullah Emin (EJFE, 2015)
The road networks are located in and around forested areas to ensure sustainable management of forest resources. However, it is crucial to improve roads due to their habitat fragmentation and the barrier effects on forest ecosystems. Especially the wild animals, as one of the important components of ecosystem, are detrimentally affected by road networks due to degradation, alteration, conversion, and loss of their habitats. In recent years, ecological infrastructures have been developed to provide wild animals with transition zones between their habitats. In this study, ecological effects of road networks on wild animals were presented, functions of ecological infrastructures were indicated, and their types were described.
Keywords: Road networks; Ecological infrastructures; Road ecology